Characterizing sample degradation from synchrotron based X-ray measurements of ultra-thin exfoliated flakes - DiScala, M. F.; Hsieh, V.; Jessen, B. S.; Gu, Y.; Rizzo, D. J.; Amontree, J. M.; Yan, X.; Wang, Q.; Kapfer, M.; Kim, T.; Geiwitz, M.; Natale, G.; et al. (Frontiers in Electronic Materials, 2025)
It is undeniable that novel 2D devices and heterostructures will have a lasting impact on the advancement of future technologies. However, the inherent instability of many exfoliated van der Waals (vdW) materials is a well-known hurdle yet to be overcome. Thus, the sustained interest in exfoliated vdW materials underscores the importance of understanding the mechanisms of sample degradation to establish proactive protective measures. Here, the impact of prolonged synchrotron-based X-ray beam exposure on exfoliated flakes of two contemporary vdW materials, NiPS3 and α-RuCl3, is explored using resonant inelastic X-ray scattering (RIXS) and total fluorescence yield X-ray absorption spectroscopy (XAS). In NiPS3, the resulting RIXS and XAS spectra show a suppression, then vanishing, of NiS6 multiplet excitations coupled with an upward shift of the peak energy of the XAS as a function of X-ray dose. In α-RuCl3, the signs of beam damage from the RIXS spectra are less evident. However, the post-experiment characterization of both materials using Raman spectroscopy exhibits signals of an amorphous and disordered system compared to pristine flakes; in addition, energy-dispersive X-ray spectroscopy of NiPS3 shows evidence of ligand vacancies. As synchrotron radiation is fast becoming a required probe to study 2D vdW materials, these findings lay the groundwork for the development of future protective measures for synchrotron-based prolonged X-ray beam exposure, as well as for X-ray free electron laser.